Indonesian Stock Market Return Volatility and Foreign Portfolio Capital: Evidence Before and During Covid-19 Pandemic - Reffi Marizka Dewi; Lukytawati Anggraeni; Tony Irawan (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
The Covid-19 pandemic increased uncertainty in the Indonesian stock market. This paper aims to investigate foreign and domestic investors' behavior in the Indonesian stock market, especially during the Covid-19 pandemic. The method used was E-GARCH and DCC-GARCH. The results showed that the impact of shocks from bad and good news was greater on the return volatility during the pandemic. The shocks had a positive impact on the increase in the spillover effect of NFI's volatility to return volatility in the short and long term before the pandemic, but this did not happen during the pandemic. There is an indication of bias of forecasting errors and prospect theory in the behavior of investors in the Indonesian stock market. Conservatism bias is also indicated in the behavior of foreign investors. Keywords: Covid-19, E-GARCH, DCC-GARCH, net foreign inflow, return volatility